Peralihan Kepemilikan Tanah Pertanian Menurut Hukum di Indonesia - adi perwira s (Fakultas Hukum Universitas Riau, 2021)
The landreform program by government requires a control of maximum area limitation over the agricultural land and prohibiting absentee ownership of land with the aim of equitable distribution of people's welfare. If this happens, the land owner has an obligation to transfer the ownership of the agricultural land to another party in accordance with the applicable regulations. However, in implementing these regulations there are still problems. This study aims to discuss the existence of these regulations and analyze the problems in their implementation. This research is a normative legal research, while the analysis method is qualitative. The results showed that there are still people who own land that exceeds the maximum allowable limit and there is still absentee ownership of land. This happened because of the inconsistencies in the prevailing rules. Likewise, regulations are not relevant to conditions in the current era of globalization 4.0 which emphasize more on strengthening the investment climate than following the rules in consistency. In addition, this happened because of the weak supervision of the authorities in charge, and indecisive actions caused by the absence of norms in the regulations applied. Thus, it is hoped that the regulation can be revised.